Increasing Capacity Building in the Implementation of Digital Service and Information Systems in Maleber Village, Ciamis District, Ciamis Regency - Brian Rizki Fauzi; Otong Husni Taufiq; Fachmi Syam Arifin (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
Digital transformation in government governance requires comprehensive preparedness from public officials at the lowest administrative level, including urban villages (kelurahan). This article examines the extent to which capacity building has been enhanced to support the implementation of digital service and information systems in Maleber Urban Village, Ciamis District, Ciamis Regency. The study employed a descriptive qualitative approach, with data collected through in-depth interviews, observations, and documentation involving six informants consisting of village officials and local community members. The analysis was conducted using Grindle’s capacity building framework, which encompasses three dimensions: human resource development, organizational strengthening, and institutional reform. The findings indicate that these three dimensions have not yet been implemented optimally. Training for officials remains entirely dependent on initiatives from the regency government, no specific Standard Operating Procedures (SOPs) for digital services have been established, coordination among units is still informal, and monitoring and evaluation mechanisms for digital programs have not been systematically implemented. These findings highlight the need for structured interventions, including independent training programs at the village level, the development of digital service SOPs, the strengthening of technological infrastructure, and the establishment of sustainable performance evaluation mechanisms. Keywords: Capacity Building, Digital Information Systems, E-Government, Public Services, Urban Village